ANALISIS PENGELOMPOKAN DERAJAT KESEHATAN IBU DAN ANAK DI INDONESIA MENGGUNAKAN STRUCTURAL EQUATION MODELING PARTIAL LEAST SQUARE-PREDICTION ORIENTED SEGMENTATION (SEM PLS-POS) - Eliani Eliani; Rais Rais; Fadjryani Fadjryani (Jurnal Matematika, Statistika dan Komputasi, 2023)
One of Indonesia's development goals in 2020-2024 is to form quality and competitive human resources. One of the efforts to achieve this goal is to improve the quality of maternal and child health. However, the issue of Maternal and Child Health (MCH) is still a challenge for the Indonesian health system. This study aims to determine the modeling and to obtain provincial groupings based on the degree of maternal and child health in Indonesia. The method used is Structural Equation Modeling Partial Least Square-Prediction Oriented Segmentation (SEM PLS-POS). The results of the PLS SEM analysis showed that the environmental variables and health services had a significant effect on the health status of mothers and children with an R2 value of 48.8%. The grouping of provinces based on the degree of maternal and child health in Indonesia using PLS-POS produces 3 segment classes. Segment 1 consists of 11 provinces, segment 2 consists of 13 provinces and segment 3 consists of 10 provinces with a large influence between different latent variables.